STUDI DESKRIPTIF FLEKSIBILITAS DISTRIBUSI PADA UD FADJAR STATIONARY, SURABAYA - Arini Kurnia Sari; Antonius Budhiman Setyawan; Veny Megawati (CALYPTRA, 2018)
Flexibility is an ability to change or act toward uncertain environment that affects to time, power, cost or performance. As one of dimension of supply chain flexibility, distribution flexibility is the ability to supply distribution in wide or intensive range. Distribution flexibility is involve physical distribution flexibility, management of demand flexibility and coordination flexibility. This research was conducted at UD Fadjar Stationary, Surabaya. UD Fadjar Stationary is retail and distributor that sells stationary and gift products.The objectives of this research are to investigate the process of gaining in deep knowledge about distribution flexibility and seeking of how UD Fadjar Stationary create and apply the strategy of distribution flexibility. This researchused explorative method by conducting an interview with the owner of UD Fadjar Stationary. From the result of this research is shown that the distribution flexibility at UD Fadjar Stationary was good enough. Even though, physical distribution flexibility and coordination flexibility were superior rather than management of demand flexibility.